Primeiro Registro de Aricoris campestris (H. Bates) (Lepidoptera: Riodinidae) em Palma Forrageira Nopalea cochenillifera (L.) Salm-Dyck (Cactaceae) no Brasil - Souza, Mileny dos Santos de; Souza, José Thyago Aires; Lima, Guilherme Ferreira Costa; Medeiros, Márcio Raimundo de; Oliveira, Robério de; Batista, Jacinto de Luna (EntomoBrasilis, 2018)
Resumo. A palma Nopalea cochenillifera (L.) foi introduzida no Brasil para produção do corante carmim, porém logo se descobriu seu potencial como forrageira. Até então, os relatos eram de que essa planta tinha como principais insetos-praga um grupo de cochonilhas. Este trabalho relata pela primeira vez a presença de Aricoris campestris (H. Bates) infestando essa cultura. First Record of Aricoris campestris (H. Bates) (Lepidoptera: Riodinidae) in Cacti Nopalea cochenillifera (L.) Salm-Dyck (Cactaceae) in Brazil Abstract. The Nopalea cochenillifera (L.) cacti was introduced in Brazil to produce the carmine dye, but soon its potential as forage was discovered. Until then reports were that this plant had as main insects-pest a group of mealybugs. This work reports for the first time the presence of Aricoris campestris (H. Bates) infesting this culture.